2020
DOI: 10.1108/ict-12-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supportive work environment on employee retention: the mediating role of person–organisation fit

Abstract: Purpose This study aims to examine the relationships for the following: supportive work environment, person–organisation fit and employee retention among academic staff in one of the Malaysian public universities. Design/methodology/approach This study used a conceptual framework to assess the direct impacts of supportive work environment (i.e. perceived climate, supervisory relationship, peer group interaction, perceived organisational support), person–organisation fit and employee retention. A self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 87 publications
0
28
0
Order By: Relevance
“…With 28.3% potential influence of SWE on performance of teachers, the findings seem to contrast a number of earlier studies. For instance, Yusliza et al (2020) found supportive work environment to be having high influence on academic stuff retention in Malaysia. Similarly findings were reported in Kundu and Lata (2017) as well as Naz et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With 28.3% potential influence of SWE on performance of teachers, the findings seem to contrast a number of earlier studies. For instance, Yusliza et al (2020) found supportive work environment to be having high influence on academic stuff retention in Malaysia. Similarly findings were reported in Kundu and Lata (2017) as well as Naz et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…This implied that the work environment (conditions of physical work environment, psychological work environment, and non-physical work environment) does not positively support the pedagogical and professional performance of teachers. In Malaysia, Yusliza et al (2020) examined the relationships between supportive work environment, person-organisation fit and employee retention among academic staff in one of the public universities. The study conceptualised supportive work environment as perceived climate, supervisory relationship, peer group interaction, and perceived organisational support.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee retention rates are also influenced by the work environment (Kundu & Lata, 2017). The work environment is everything outside the organization that has the potential to affect employees at work and ultimately affect organizational performance (Yusliza et al, 2021). The work environment is divided into a physical work environment and a non-physical work environment.…”
Section: Introductionmentioning
confidence: 99%
“…value of conformity between the organization and employees(Yusliza et al, 2020). The organization supports a conducive work climate through ethical standards, upholding honesty, implementing a mandate, and strengthening individual values' conformity with organizational expectations.…”
mentioning
confidence: 99%